Assessment of the potential relationship between egg quality and infectious bronchitis virus infection in Australian layer flocks. Issue 4 (April 2014) - Hewson, KA; Robertson, T; Steer, PA; Devlin, JM; Noormohammadi, AH; Ignjatovic, J
<x xml:space="preserve">Abstract</x> Objective This investigation aimed to determine if there was a relationship between the production of eggs with poor internal quality, as measured by poor Haugh units, by Australian layer flocks and the detection of infectious bronchitis virus (IBV) in the hens. Other risk factors including flock size, flock type, flock age, chicken breed and vaccination frequency were also assessed. Methods The study group comprised 17 flocks from 14 farms. Data relating to the factors investigated were requested on a regular basis. The Haugh unit data were used to grade eggs as good or poor based on the age and flock at the time of data collection. Cloacal swabs were collected from 20 chickens in each flock approximately every 6 weeks. Results IBV was detected from a majority of the flocks and in 68% of cases the IBV strain detected was an A‐vaccine‐related field strain. Three variant strains were detected. Detection of IBV in a flock, the farm type and flock size were identified as potential risk factors for the production of eggs with poor Haugh units. Conclusion IBV is prevalent in Australian layer flocks, but infection was primarily subclinical. The results complement previous reports indicating that there are many potential risk factors for the production of eggs with poor Haugh units.